Orthogonality of silver-ion and non-aqueous reversed-phase HPLC/MS in the analysis of complex natural mixtures of triacylglycerols - Holcapek, Michal; Velínská, Hana; Lísa, Miroslav; Cesla, Petr (Journal of separation science, 2009)
The goal of this work is the study of possibilities of two basic separation modes used in the analysis of complex triacylglycerol (TG) samples of plant oils and animal fats, i.e. non-aqueous reversed-phase (NARP) and silver-ion HPLC coupled with atmospheric pressure chemical ionization mass spectrometry (APCI-MS). The orthogonality of both separation modes is tested for complex TG mixtures containing fatty acids (FAs) with different acyl chain lengths, different number, positions and geometry of double bonds (DBs) and different regioisomeric positions of FAs on the glycerol skeleton. The retention in NARP mode is governed by the equivalent carbon number, while the retention in silver-ion chromatography increases with the increasing number of DBs with a clear differentiation between cis- and trans-FAs. Moreover, silver-ion mode enables at least the partial resolution of regioisomeric TG mixtures including cis-/trans-regioisomers, as illustrated on two examples of randomization mixtures. Off-line 2D coupling of both complementary modes (NARP in the first dimension and silver-ion in the second dimension) yields the superior chromatographic selectivity resulting in the highest number of identified TGs ever reported for studied samples. Off-line 2D chromatograms are processed with the home-made software providing various ways of data visualization.
Keywords: Chromatography, High Pressure Liquid; Plant Oils; oleje rostlin; hmotnostní spektrometrie; Silver; Animals; stříbro; Mass Spectrometry; zvířata; triglyceridy; Triglycerides; vysokoúčinná kapalinová chromatografie